STZ causes depletion of immune cells in sciatic nerve and dorsal root ganglion in experimental diabetes - Hidmark, Asa S.; Nawroth, Peter Paul; Fleming, Thomas (Journal of neuroimmunology, 2017)
Streptozotocin (STZ) treatment, a common model for inducing diabetes in rodent models, induces thermal hyperalgesia and neuronal toxicity independently of hyperglycemia by oxidizing and activating TRPA1 and TRPV1. Following treatment with STZ, CD45+ immune cells were found to be depleted in sciatic nerve (SN) and DRG in mice, prior to hyperglycemia. Macrophages were also lost in DRG and NFκB-p65-activation was increased in SN macrophages. Immune cells were significantly reduced in both SN and DRG up to three weeks, post-treatment. Loss of PNS-resident macrophages in response to STZ-mediated toxicity may affect the regenerative capacity of the nerve in response to further injury caused by diabetes.